KARAKTERISTIK TANAH PADA LAHAN KERING DI DESA TISTA KECAMATAN BUSUNGBIU KABUPATEN BULELENG (THE SOIL CHARACTERISTICS ON DRY LAND AT TISTA VILLAGE, BULELENG REGENCY) - KUSMIYARTI, TATI BUDI (AGRITROP, 2012)
The purpose of the research was to know the characteristics and classification of soil on dry land at Tista village, Buleleng Regency. Soil survey methods and analysis in laboratory were used in this research. Some parameters of soil properties were observed i.e. soil morphology in the field, physical, chemical, and mineralogical soil properties in the laboratory. Soil classification based on Soil Taxonomy system by using Keys to Soil Taxonomy (2003). The soil characteristic on Dusun Tista, Tista village are: solum depth is deep; clay loam texture and c-organic are high; CEC is high; base saturation is high. The soil characteristic on Dusun Sepang Kelod, Tista village are: solum depth is deep; loam texture and c-organic are high; CEC is high; base saturation is high; and Al + ½ Fe is high. There were two soil families in Tista villages, namely: Andic hapludepts, fine loamy, mixed, isohyperthermic, and Typic hapludepts, fine loamy, mixed, isohyperthermic.
Keywords: soil characteristic, Tista village